2010
DOI: 10.1097/ftd.0b013e3181c3a16d
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin in Lymphoma: Association Between Pharmacokinetic Variability and Clinical Response

Abstract: Despite many years of clinical use in Hodgkin lymphoma, no previous studies have evaluated the relationship between doxorubicin pharmacokinetics and clinical response. In a pilot study, we associated the area under the curve of doxorubicin with successful remission. Patients with successful remission (n = 14) had a trend toward a higher median area under the curve than those who failed remission (n = 4; 36,390 versus 19,350 ng/mL x minute, P = 0.08, respectively). Median peak serum concentrations were 73 ng/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
1
7
0
2
Order By: Relevance
“…Elis et al recently reported on the association between doxorubicin AUC and clinical response in 19 non-pregnant adult patients with Hodgkin’s lymphoma [38]. Using the same method to estimate the AUC in our subjects who were treated with short-term infusion, the values were within or greater than the range previously reported (274-742 ng•hr/mL).…”
Section: Discussionsupporting
confidence: 71%
“…Elis et al recently reported on the association between doxorubicin AUC and clinical response in 19 non-pregnant adult patients with Hodgkin’s lymphoma [38]. Using the same method to estimate the AUC in our subjects who were treated with short-term infusion, the values were within or greater than the range previously reported (274-742 ng•hr/mL).…”
Section: Discussionsupporting
confidence: 71%
“…They demonstrated that successful remission was associated with a higher median AUC. Those with median serum concentration of 280 ng/ml obtained successful remission compared with those who failed remission with median concentration of 73 ng/ml [145]. The authors concluded that TDM of doxorubicin may be warranted in patients with Hodgkins lymphoma, due to the wide variability observed in interindividual pharmacokinetics.…”
Section: Doxorubicinmentioning
confidence: 96%
“…There have been very few studies of the relationship between doxorubicin pharmacokinetics and clinical response. A recent study of doxorubicin by Elis et al studied the association of doxorubicin pharmacokinetics with remission rates in Hodgkins lymphoma patients [145]. They demonstrated that successful remission was associated with a higher median AUC.…”
Section: Doxorubicinmentioning
confidence: 98%
“…Many factors such as patient demographics (age, gender, and body surface area), genetics, and the environment are known to alter the PK of a drug. Hence, these factors serve as potential causes of the inter-patient PK and PD variability associated with anticancer agents [1, 6, 7]. …”
Section: Introductionmentioning
confidence: 99%